Model Pembelajaran Berbasis Masalah (Problem Based Learning) dalam Pembelajaran Bahasa Asing di Perguruan Tinggi - Saleh, Nurming; Usman, Misnawaty; Achmad, Abd. Kasim; Nursalam, Nursalam (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2023)
This research is a collaborative scientific and qualitative study (mixed method) using the concurrent transformative strategy method, which aims to obtain data and information related to the effectiveness of problem-based learning models in foreign language learning in higher education. The research was conducted at the Department of Foreign Language Education, Faculty of Language and Literature, State University of Makassar. The population of this study is all students in the even semester of the 2021/2022 academic year. This study's sample is all students in the second semester of the German, Arabic, and Chinese Language Education Study Program. Research data were obtained from participatory observations, tests and documentation. The instrument of this study is an observation sheet for learning activities and competency tests for foreign languages (German, Arabic, and Chinese). The qualitative data of this study were analysed using the Miles and Hubermann model, which consisted of four stages: data collection, data reduction, data presentation and conclusion. Meanwhile, the research data were analysed using IBM SPSS 26. The study results show that students' foreign language competence through a problem-based learning model is in the moderate category. The average effect of learning German for students was 78.87. The average score of students was 78.43, and students' Chinese outcomes were 78.95. Related to the effectiveness of problem-based learning models on foreign language learning, on German language learning, problem-based learning models are effective in listening competence, writing skills and speaking skills. Problem-based learning models could be more effective against reading competence. The problem-based learning model for Arabic and Chinese improves writing and speaking skills. The learning model could be more effective in listening and reading competencies.